Batch studies of lead adsorption from a multi-component aqueous solution onto Atlantic cod fish scale (Gadus morhua) substrate. Issue 4 (1st July 2007) - Basu, A; Rahaman, M S; Mustafiz, S; Islam, M R
Abstract : Aqueous streams often posses several contaminants that are of environmental concerns. Removing these contaminants from the multi-component phases is a challenging task. In this study, the multi-component (combination of lead and arsenic ions) batch adsorption results are analyzed with respect to initial concentrations of the contaminants (lead: 2.5, 10, and 40 mg/L; arsenic: 350 and 1000  μ g/L) and pH variations (pH value of 4, 7, 9, and 11) of the bulk phase. The adsorbent selected for this research is Atlantic cod ( Gadus morhua ) fish scale. A general trend of reduced lead adsorptivity with increasing arsenic concentration is observed at the lower concentration of 2.5 mg/L of the heavy metal cation. The decrease in lead to arsenic concentration ratio in the bulk phase is correlated with an increase in "electrostatic attractions" or with "ion pair bridging" by the arsenic species on lead ions. However, at higher lead ion concentrations of 10 ppm and 40 ppm, the effect of arsenic on lead adsorption is insignificant. Key words: adsorption, arsenic, Atlantic cod fish scale, bio-sorption, lead, concentration ratio.